Pathways for labor migration from Northern Central America: Five difficult but necessary proposals - Michael A. Clemens (Institute of Labor Economics (IZA), 2022)
Very few labor-based pathways for regular migration are available for people in Northern Central America, often called the 'Northern Triangle' of Guatemala, Honduras, and El Salvador. This note briefly summarizes the state of labor-based migration channels in the region. It then argues that extending those channels is a necessary complement to asylum reform even for the goal of humanitarian protection. It concludes by arguing that five recommendations for long-term reform, though difficult, are needed to unleash the maximum shared benefit of these pathways.
Keywords: F22; J61; O15; 330; migration; migrant; immigrant; irregular; illegal; unauthorized; undocumented; pressure; development; restrictions; visa; regulation; border; crisis; channels; smugglers; clandestine; Central America; Latin Americastine